Civil commitment of sexual predators: a study in policy implementation - Harris, Andrew J. R. (Criminal justice, 2005)
State of current knowledge -- SVP civil commitment policies in an implementation framework -- Methodological approach -- Conceptual and operational models -- Conceptual analysis -- Operational analysis -- Summary and conclusions.